A review of the structured framework for sustainability audits in manufacturing organizations - Dharmendra Hariyani; Poonam Hariyani; Sanjeev Mishra; Milind Kumar Sharma (Green Technologies and Sustainability)
In the rapidly evolving field of sustainability, the manufacturing system plays a vital role in shaping an organization’s environmental, social, and economic outcomes. Manufacturing organizations are continuously working to enhance their sustainability performance and meet stakeholders’ expectations. Despite these growing efforts, the existing literature reveals significant gaps in methodologies and guidelines for effective audits. This underscores the need for a structured audit system and clear guidelines to assess the sustainability practices of manufacturing organizations. Synthesizing insights from 448 Scopus-indexed studies, this study presents a comprehensive audit system or framework that encompasses pre-audit preparation, on-site evaluation, and post-audit reporting. It offers actionable strategies for enhancing sustainability practices, mitigating risks, and creating long-term stakeholder value. The study also highlights the transformative role of digital technologies, such as real-time monitoring systems, AI-driven analytics, and blockchain, in streamlining audit processes, improving data accuracy, and fostering greater transparency. By adopting these advancements, manufacturing organizations can better monitor performance, align operational goals with sustainability benchmarks, and adapt to emerging challenges. Future research directions include integrating circular economy principles, leveraging advanced analytics, and expanding social impact assessments to ensure the auditing system evolves in line with sustainability imperatives, such as addressing sustainability challenges and seizing opportunities. This study addresses critical gaps in the literature and provides a roadmap for policymakers, industry leaders, and researchers to drive impactful improvements, contributing to a resilient and sustainable future for the manufacturing sector.